Phylogeny of the subfamily Mycetophilinae (Diptera: Mycetophilidae) - Rindal, Eirik; Søli, Geir E.e. (Zootaxa, 2006)
A phylogenetic analysis of the Mycetophilinae is presented and discussed. The analysis is based on morphological characters for 27 genera. Fourteen equally parsimonious trees were found. The monophyly of the Mycetophilinae and the two tribes, Exechiini and Mycetophilini, is well supported. Within the Exechiini, good support for the sister-group relationship of Exechia and Exechiopsis was found, as was support for the inclusion of Cordyla in the tribe. The analysis provides good resolution within the Mycetophilini, with Trichonta as the sister group of the remaining taxa.